2014
DOI: 10.1021/jp500824e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Belousov–Zhabotinsky Substrate Concentrations on Autonomous Oscillation of Polymer Chains with Fe(bpy)3Catalyst

Abstract: We studied the effect of initial substrate concentrations in the Belousov-Zhabotinsky (BZ) reaction on the optical transmittance self-oscillation behavior of a polymer chain consisting of N-isopropylacrylamide (NIPAAm) and a Fe catalyst ([Fe(bpy)3]). The driving force of this transmittance self-oscillation was the solubility difference between the reduced and oxidized states of the [Fe(bpy)3] moiety in the polymer chain. The amplitude of the soluble-insoluble self-oscillation of poly(NIPAAm-co-[Fe(bpy)3]) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Some of them have been recently exploited for the design of SOPs. Hara et al [14,15] demonstrated that Ru(bpy) 3 catalyst could be substituted by Fe(bpy) 3 . Although the utilization of iron greatly lowers the cost for preparing the BZ reaction catalyst, the soluble-insoluble self-oscillating amplitude is smaller than that of Ru(bpy) 3 -based copolymer.…”
Section: +mentioning
confidence: 99%
“…Some of them have been recently exploited for the design of SOPs. Hara et al [14,15] demonstrated that Ru(bpy) 3 catalyst could be substituted by Fe(bpy) 3 . Although the utilization of iron greatly lowers the cost for preparing the BZ reaction catalyst, the soluble-insoluble self-oscillating amplitude is smaller than that of Ru(bpy) 3 -based copolymer.…”
Section: +mentioning
confidence: 99%
“…To apply the self-oscillating polymer system to devices such as an autonomous pump system, the cost of the Ru(bpy) 3 moiety was regarded a problem because Ru is a rare metal. To reduce the cost of the metal catalyst moiety in the self-oscillating polymer system, Hara et al first synthesized a self-oscillating polymer chain with an Fe catalyst moiety (Fe(bpy) 3 ) for the BZ reaction [15,16]. In this study, the optical self-oscillating behaviors of the polymer chain with Fe(bpy) 3 were measured at constant concentrations of the three BZ substrates (malonic acid (MA; 0.1 M), sodium bromate (NaBrO 3 ; 0.2 M), and sulfuric acid (H 2 SO 4 ; 0.2 M)) and at constant several temperatures (T = 11, 12, 13, 15, 17, and 19°C).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the optical self-oscillating behaviors of the polymer chain with Fe(bpy) 3 were measured at constant concentrations of the three BZ substrates (malonic acid (MA; 0.1 M), sodium bromate (NaBrO 3 ; 0.2 M), and sulfuric acid (H 2 SO 4 ; 0.2 M)) and at constant several temperatures (T = 11, 12, 13, 15, 17, and 19°C). In previous studies [15,16], nitric acid was used as the strong acidic agent for the BZ reaction. In this study, we selected sulfuric acid as the strong acidic agent to confirm the influence of the oxidation power on the self-oscillating behavior of the polymer solution with Fe(bpy) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to construct a self-oscillating polymer system with a cheap metal catalyst moiety in order to expand its application. Recently, Hara developed a novel self-oscillating polymer by covalently bonding the Fe(bpy) 3 moiety to the polymer chain, which acted as the metal catalyst for the BZ reaction [27,28]. However, the amplitude of the soluble-insoluble self-oscillation of poly(NIPAAm-co-[-Fe(bpy) 3 ]) was significantly smaller than that of the corresponding Ru-based self-oscillating polymer system.…”
Section: Introductionmentioning
confidence: 99%